Heat Transfer Modeling in Soil Microwave Heating - Fabio Fanari; Chiara Dachena; Renzo Carta; Francesco Desogus (Chemical Engineering Transactions, 2019)
The agricultural neediness of cost-effective, environmental friendly and chemical-free methods for farmlands disinfection led to the development of microwave-based solutions, an efficient way of directly conveying energy to the target. Harmful agents such as weeds pests, fungi and bacteria can be suppressed heating the contaminated soil up to pasteurization or sterilization temperatures by irradiating electromagnetic energy by an antenna. The treatment can be carefully devised and designed optimizing the temperature distribution and calibrating the exposure time depending on the soil characteristics, and on the environmental and boundary conditions. In this work a computational model to solve the non-linear multi-physic dielectric heating phenomenon is presented, so taking into account the temperature dependence of the dielectric and thermal soil properties, in order to demonstrate the possibility of properly tuning the microwave application depending on the external heat transfer conditions. It was found that, in the specific conditions here analyzed, an increase of the external convection heat transfer coefficient up to 50 W·m-2·K-1, despite being a possible critic condition for the surface, brings to the possibility of treating a soil layer of higher thickness, up to 20 cm. On the other hand, doubling the microwave power from 12 to 24 kW·m-2 generally reduces the treatment time to less than half, with overall energy savings.